Covid-19: Challenges on Undergraduate Research Students to an Online Learning Mode - Aziz, Nur Mardhiyah; Jabar, Izatul Laili (Built Environment Journal, 2024)
The profound impact of Coronavirus Disease 2019 (COVID-19) affects people's health, work, lives, and how people learn. The switch from the current physical learning to a new system poses several challenges. This research focuses on identifying the challenges faced by the students in adapting to an online learning mode and how these challenges impacted the completion of their dissertations. An initial list of the challenges faced by students in completing the dissertation was identified from the literature review. This list was followed by developing a questionnaire survey distributed to thirty-seven (37) Quantity Surveying students who registered for the dissertation subject in semester two (2), session 2020/2021. The data obtained were analysed descriptively. Results show that the primary concern is not about having a suitable device to be used during the learning process but more on the other factors such as the inability to access the right software for data analysis, difficulty in collecting the data due to the movement restriction, a quiet place to study, stable internet connection, difficulty to stay focused and motivated to do the research, time management, stress and did not know where to go for help. The implications of the findings imply that the university should take necessary action based on the identified challenges in reducing the effects on the students.